(untitled) (Bangladesh Journal of Medical Science, 2024)
Objective: Nursing care is a unique and indispensable concept for nursing that includes helping to meet the needs of an individual or a group of individuals offered by nurses. This study is aimed to test the validity and reliability of the Turkish version of the Quality Nursing Care Scale (QNCS-T). Materials and Methods: The methodological approach employed in this study spanned from April 25, 2021, to May 5, 2021, and enlisted the participation of 347 nurses. Data collection was executed utilizing a “Personal Information Form” and the “Quality Nursing Care Scale (QNCS).” The research comprised two phases: Phase 1 involved the adaptation of the scale, while Phase 2 focused on determining construct validity through confirmatory factor analysis. Reliability was assessed through measures of internal consistency and item-total correlation coefficients. Results and Discussion: The adaptation phase yielded affirmative outcomes, affirming the linguistic and content validation of the Turkish version of the scale. Confirmatory factor analysis demonstrated a highly favorable fit for a six-factor model. The Cronbach’s alpha coefficient for the entire scale was determined to be 0.93, attesting to its strong internal consistency. Conclusion: The Turkish version of the Quality Nursing Scale showed consistently good psychometric properties of reliability and validity. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 826-833